Real-life data on the efficacy and safety of ombitasvir/paritaprevir/ritonavir + dasabuvir +ribavirin in the patients with genotype 1 chronic hepatitis C virus infection in Serbia - Simonović-Babić Jasmina; Bojović Ksenija; Fabri Milotka; Cvejić Tatjana; Svorcan Petar; Nožić Darko; Jovanović Maja; Škrbić Ranko; Stojiljković Miloš P.; Mijailović Željko (Vojnosanitetski Pregled)
Background/Aim. The era of direct-acting antiviral (DAA) regimen in the treatment of chronic hepatitis C virus (HCV) started in 2011. The aim of this study was to assess the antiviral efficacy and safety of DAA regimen, ombitasvir (OBV)/paritaprevir (PTV)/ritonavir (r) + dasabuvir (DSV) + ribavirin (RBV), in patients with chronic HCV infection, genotype 1. Methods. The real-life data were collected. The study was multicentric and included seven infectious diseases and hepatology departments in Serbia. A total of 21 patients were enrolled in the OBV/PTV/r + DSV + RBV early access program, 20 of which were previously treated with pegylated interferon + RBV, while 1 was treatment-naive. All patients received the adequate doses of these antiviral drugs. RBV was not given to the patients with HCV genotype 1b infection according to the therapeutic protocol. For the majority of patient, the treatment duration lasted for 12 weeks. For the patients with liver cirrhosis, who were infected with HCV genotype 1a, the duration of treatment was 24 weeks. Viremia was assessed at four points in time: at baseline, 4 weeks after the treatment beginning (rapid viral response, RVR), 12 or 24 weeks after the treatment beginning (end of treatment response – ETR) and 12 weeks after the end of treatment (sustained viral response – SVR). SVR, as a confirmation of the absence of HCV was considered as endpoint of successful treatment. Results. Complete RVR, ETR and SVR were achieved in 64.71%, 85.71% and 95.24% of the patients, respectively. Only 3 patients had mild adverse effects which did not required dose reduction. Conclusion. The treatment of the patients with a chronic HCV infection with OBV/PTV/r + DSV + RBV resulted in excellent antiviral activity and tolerability.